A crítica da forma do fenômeno jurídico na atuação do Poder Judiciário de Mato Grosso em relação à greve de 2019 dos professores públicos estaduais - Araújo, Rodrigo de Freitas Silva (2021)
This dissertation reflects on the relationship between Capital and the Legal Phenomenon. Its general objective was to analyze the form of the legal phenomenon and how its development in the capitalist mode of production is reflected in the performance of the Judiciary and how this is put into practice by the magistrates that make up the District of Cuiabá as well as the Court of Justice, in relation the strike of teachers in the State of Mato Grosso in 2019. For this, we developed a qualitative research, adopting as theoretical foundation authors such as Pachukanis (2017), Marx (2017, 2012, 2010, 2008, 2005, 2004), Marx and Engels (2011, 1998), Althusser (1985), among others, who discuss the Critical Theory of Law and Historical and Dialectical Materialism. Also as part of the methodological procedures, we carried out data collection and analysis of court decisions that took place during the period of the teachers' strike. For the analysis of this material, the Nvivo 12 software was used, with the interest of knowledge in the information about the emancipation and empowerment of the working class, in particular, teachers from the Public Network of the State of Mato Grosso. Still as methodological procedures at the end, the most repeated words found in court decisions related to the categories were grouped together: Capitalist State, Commodified Labor, Subjects of Law, Legal Phenomenon and Ideology, thus evidencing the link between capital and the legal phenomenon in its movement real and in all its concreteness. In the conclusion it was verified that the Legal Phenomenon was an instrument of legitimization of the domination of the working class by the bourgeois class, constituting itself as a politicallegal superstructure and at the same time an ideological superstructure, based on the form of mercantile equivalence.